The dynamics of product innovation and firm competences - Danneels, Erwin (Strategic Management Journal, 2002)
Abstract This study examines how product innovation contributes to the renewal of the firm through its dynamic and reciprocal relation with the firm's competences. Field research in five high‐tech firms of varying age, size, and level of diversification is combined with analysis of existing theory to develop the findings of the study. Based on the notion that new products are created by linking competences relating to technologies and customers, a typology is derived that classifies new product projects based on whether a new product can draw on existing competences, or whether it requires competences the firm does not yet have. Following organizational learning theory, these options are conceptualized as exploitation and exploration. These organizational learning concepts are used to gain a dynamic and path‐dependent view of product innovation and firm development, and to reveal the unique nature and challenges of different types of product innovation. Copyright © 2002 John Wiley & Sons, Ltd.